Endoscopic ablation systems. (March 2013) - Bordignon, Stefano; Chun, Kyoung-Ryul Julian; Gunawardene, Melanie; Schulte-Hahn, Britta; Nowak, Bernd; Fuernkranz, Alexander; Schmidt, Boris
Pulmonary vein (PV) isolation for ablation of atrial fibrillation is a well-accepted therapy option for high symptomatic patients refractory to antiarrhythmic drugs. Radiofrequency point-by-point ablation is the gold-standard technique; however, in the last two decades, many new technologies have been developed. The endoscopic ablation system makes direct PV ostium visualization possible, despite the large anatomy variation thanks to its compliant balloon. The laser generator delivers precise lesions that in the first clinical studies seem to be durable, with a safety and efficacy profile similar to the other PV isolation techniques. If these early results are confirmed by larger clinical studies, the endoscopic ablation system will offer a new paradigm in ablation of cardiac arrhythmias by directly visualizing the target substrate.